تطبيق طريقة " أمثلتي" في تنمية التفكير الناقد في تعلم النحو لدى طلاب المعهد الإسلامي تربية العلوم سومورسونجو ماجيتان - Ubaidillah Mufidh, Zulfa (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
The background to this research is that Arabic ranks second as the most difficult language in the world, so Muslims all over the world are competing to develop a method to make it easier for Muslims to learn Arabic, especially Nahwu and Shorof. One of them is the amtsilati method, a method that is considered successful as proven by the number of Islamic boarding schools in Indonesia that use this method. In this regard, the researcher chose the Tarbiyatul Ulum Sumursongo Islamic Boarding School as the object for researching the amtsilati method. The objectives are: 1) To find out the application of the amtsilati book to improve critical thinking skills in nahwu learning at the Tarbiyatul Ulum Sumursongo Islamic Boarding School 2) To find out the advantages and disadvantages of learning nahwu using the amtsilati book at the Tarbiyatul Ulum Sumursongo Islamic Boarding School. This research method uses a qualitative descriptive approach. The main data source is the teacher from the amtsilati method. Data collection techniques use observation, interviews, documentation. Data analysis uses data condensation, data presentation, drawing conclusions. Research results: 1) Amtsilati is taught as a subject at Madrasah Diniyyah and is taught twice a week, the time allocation for each meeting is 90 minutes. 2) Amtsilati has the advantage of its materials which are summaries of the nahwu and shorof books which are mu'tabar and there are nadhom nadhom with Javanese translations which make it easier to understand. As for the drawbacks, amtsilati only teaches the basic material of nahwu and shorof, amtsilati also requires the material to be taught repeatedly